If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + -19 = 19 Reorder the terms: -19 + Z = 19 Solving -19 + Z = 19 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + Z = 19 + 19 Combine like terms: -19 + 19 = 0 0 + Z = 19 + 19 Z = 19 + 19 Combine like terms: 19 + 19 = 38 Z = 38 Simplifying Z = 38
| 2(x+6)=-2x(x-4) | | 5.25=1.25 | | 5[x+9]=80 | | Y=5.5x+15 | | X+0.5y=7 | | 3C+7+5c=4c+31 | | 8x+-2=60 | | 6x+2=8x-26 | | (3x+4)(x^2+14x+40)=0 | | 5/2u=20 | | 5i/8-3i | | 2(i+2)-9=-17-i | | 7x/2=(5x-4)/3 | | ln(x)+ln(x+-6)=ln(8x-24) | | 15x^2+x=75 | | -105=-7(2k+1) | | (x+3)+2=0 | | 11x-2+6x+7=90 | | (3y+5)+(2x+1)=85 | | 28-42=154 | | 6x-48=66 | | .25(16+12x)=28 | | 180-x/2=2(90-x)-24 | | 4x+3y+2z=24 | | 8x-4=56 | | -5y+44=4(y+2) | | -5.1z=-11.53 | | 180-x/2=180-2x-24 | | y^3+0.4898=5.02*y^2 | | 3(y-7)=-2y+24 | | 2.25+.20x=7.65 | | 3(y-7)=2y+24 |